2002
DOI: 10.1677/joe.0.1740335
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-hormone interaction in the ovine liver: methionine supply selectively modulates growth hormone-induced IGF-I gene expression

Abstract: This study tested the hypothesis that specific amino acids are responsible for modulating the insulin-like growth factor-I (IGF-I) response to growth hormone (GH) in ovine hepatocytes. Cells were grown in media of defined amino acid composition, based on physiological concentrations (P.C.) of amino acids in sheep plasma. Relative to culture in 5 P.C., amino acid limitation to 0·2 P.C. had inhibitory effects on IGF-I RNA expression, peptide release and p70 S6 kinase phosphorylation (P<0·01 in each case). Limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Methionine metabolism is abnormal in long-lived mutant mice that are deficient in growth hormone, prolactin and thyroid stimulating hormone (Uthus and Brown-Borg 2003;Brown-Borg et al 2005;Uthus and Brown-Borg 2006). Furthermore, methionine restriction specifically inhibits the induction of IGF-I expression by growth hormone in pig hepatocytes (Stubbs et al 2002), indicating a potential regulatory interaction of methionine metabolism on the growth hormone-IGF-I signaling pathway. It is also conceivable that methionine restriction could impact on the amino acid (leucinesensitive) TOR pathway, if only through indirect effects on branched chain amino acid metabolism Kimball and Jefferson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Methionine metabolism is abnormal in long-lived mutant mice that are deficient in growth hormone, prolactin and thyroid stimulating hormone (Uthus and Brown-Borg 2003;Brown-Borg et al 2005;Uthus and Brown-Borg 2006). Furthermore, methionine restriction specifically inhibits the induction of IGF-I expression by growth hormone in pig hepatocytes (Stubbs et al 2002), indicating a potential regulatory interaction of methionine metabolism on the growth hormone-IGF-I signaling pathway. It is also conceivable that methionine restriction could impact on the amino acid (leucinesensitive) TOR pathway, if only through indirect effects on branched chain amino acid metabolism Kimball and Jefferson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I release mechanism is induced by GH and it is interfered by methionine concentrations. Animals fed low-content total amino acid diet showed no reduction on IGF-I release, suggesting a selective methionine-inhibitory response to GH transcription factor interference in liver IGF-I gene expression (Stubbs et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Methionine supplementation interferes in growth factor regulation such as, GHR and IGF-I, and this action of methionine may be related to the activity of mTOR (mammalian target of rapamycin). mTOR is an enzyme involved in protein synthesis regulation by mechanisms dependent or not on insulin (Stubbs et al, 2002). Amino acids act not only in translation initiation and on elongation factors, but amino acids also act on signaling pathways for the synthesis of proteins that were previously thought to be influenced only by hormones (Kimball and Jefferson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although how changes in amino acid supplementation can initiate changes in expression of genes such as GH and IGF-I is not yet fully clarified, it is suggested that the mammalian target of rapamycin (mTOR) activity, an enzyme involved in regulating protein synthesis, may mediate this effect (Stubbs et al 2002).…”
Section: Discussionmentioning
confidence: 99%